Microsporidia Current Advances in Biology - Weiss, Louis M.; Reinke, Aaron W. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an up-to-date overview on the biology of microsporidia, focusing on areas where significant progress has been made in recent years. In particular, our understanding of the evolutionary position and the role of genome reduction in the biology of these enigmatic intracellular pathogens is discussed. This book also offers important updates on the mechanisms used by these organisms to modify the host cell biology of mammals, insects, nematodes, and aquatic animals, as well as the mechanisms controlling infection and host specificity. Readers gain a detailed overview of the structure and function of the polar tube, the unique invasion apparatus of microsporidia, as well as the physics and dynamics of spore firing. Particular attention is given to chronic infections in mammals caused by microsporidia, as well as common immune responses. Written by an international team of authors representing the main research groups working on microsporidian biology, this book is a valuable resource for health management professionals, experienced microbiologists, and early career scientist alike who want to learn more about these fascinating parasites. The ideas and latest finding covered in this book contribute to UN Sustainable Development Goal 3: Good Health and Well-Being. Chapter "Impact of Genome Reduction in Microsporidia" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Chapter 1: Impact of genome reduction in microsporidia -- Chapter 2: Comparative genomics of microsporidia -- Chapter 3: Insights into microsporidia evolution from early diverging microsporidia -- Chapter 4: Factors that determine microsporidia infection and host specificity -- Chapter 5: Insights from Caenorhabditis elegans into microsporidia biology and host-pathogen relationships -- Chapter 6: Advances in the genetic manipulation of Nosema bombycis -- Chapter 7: Nosema apis and N. ceranae infection in honey bees: a model for host-pathogen interactions in insects -- Chapter 8: The Function and Structure of the Microsporidia Polar Tube -- Chapter 9: Mechanics of microsporidian polar tube firing -- Chapter 10: Microsporidian Pathogens of Aquatic Animals -- Chapter 11: Recent Advances with Fish Microsporidia -- Chapter 12: Chronic Infections in mammals due to microsporidia -- Chapter 13: Immune responses to microsporidia -- Chapter 14: A perspective on the molecular identification, classification and epidemiology of Enterocytozoon bieneusi of animals.
Keywords: Parasitology; Microbiology; Medical microbiology; Parasitology; Microbiology; Medical Microbiology